5PSQ-059 Pharmacist-led observational study on quality of life in relapsing–remitting multiple sclerosis: evidence from the Qosmos study. (24th March 2020) - Damuzzo, V; Mengato, D; Milani, F; Agnoletto, L; Freddi, N; Rampazzo, R
Abstract : Background and importance: Patient reported outcomes (PRO) are increasingly used to evaluate effectiveness of treatments for multiple sclerosis (MS) and they often include an evaluation of health related quality of life (QoL). In 2017, the Italian Society of Clinical Pharmacy and Therapeutics (SIFaCT) and the National Association of Hospital Pharmacy Students (ReNaSFO) established a joint action to update existing data on QoL and its correlation with use of disease modifying drugs in Italian patients. The results will be helpful as reference for future studies using PRO. Aim and objectives: The primary endpoint was QoL score in MS patients. Secondary objectives included QoL correlation with pharmacological therapy and clinical characteristics of patients. Material and methods: We designed a multicentre, observational, cross sectional study. Every patient had to complete a questionnaire on QoL (MS-QoL54) and the pharmacist collected the following data: sex, age, MS type, expanded disability status scale (EDSS) and history of pharmacological treatments. The study was approved by an ethic committee in each centre and patients provided signed informed consent. As MS-QoL54 scores were not normally distributed, we used Spearman's correlation test, ANOVA on ranks for multiple comparisons and the Mann–Whitney test for simple comparisons. Results: We enrolled 341 patients from 16 centres (median age 44.1 years; 68.9% women) with relapsing–remitting MS from May 2018 to June 2019 (median 20 per centre). The composite indexes of physical and mental well being were correlated with each other (R=0.826; p<0.001) according to a direct proportionality, and both had an inverse correlation with the degree of EDSS disability (R=−0.511, p<0.001 and R=0.344, p<0.001, respectively). Although there was no correlation between QoL and route of administration of the drug, we found significantly lower scores for patients treated with teriflunomide compared with other oral drugs (54.24 points vs 67.64 for fingolimod and 78.25 for dimethyl-fumarate; p=0.002). Conclusion and relevance: The study achieved primary and secondary endpoints and indicated a relevant decrease in QoL related to physical health associated with teriflunomide, which deserves further investigations. We also demonstrated that joint action by a scientific society and a student association was a valuable method to perform a no profit, multicentre, observational study in real practice. References and/or acknowledgements: 1. Horta-Hernadez AM, et al. Health-related quality of life in multiple sclerosis patients treated with disease-modifying therapies. EJHP 2019;26(Suppl 1):A1–A311. https://ejhp.bmj.com/content/26/Suppl_1/A131.2 No conflict of interest.